Protocol for an HIV Pre-exposure Prophylaxis (PrEP) Population Level Intervention Study in Victoria Australia: The PrEPX Study - Ryan, Kathleen E.; Mak, Anne; Stoove, Mark; Price, Brian; Fairley, Christopher K.; Ruth, Simon; Lal, Luxshimi; Asselin, Jason; El-Hayek, Carol; Nguyen, Long; Batrouney, Colin; Wilson, David; et al. (Frontiers in Public Health, 2018)
Background: Pre-exposure prophylaxis (PrEP) is the use of HIV anti-retroviral therapy to prevent HIV transmission in people at high risk of HIV acquisition. PrEP is highly efficacious when taken either daily, or in an on-demand schedule. In Australia co-formulated tenofovir-emtricitabine is registered for daily use for PrEP, however, this co-formulation is not listed yet on the national subsidized medicines list. We describe a study protocol that aims to demonstrate if the provision of PrEP to up to 3800 individuals at risk of HIV in Victoria, Australia reduces HIV incidence locally by 25% generally and 30% among GBM. Methods: PrEPX is a population level intervention study in Victoria, Australia in which generic PrEP will be delivered to 3800 individuals for up to 36 months. Study eligibility is consistent with the recently updated 2017 Australian PrEP guidelines. Participants will attend study clinics, shared care clinics, or outreach clinics for quarterly HIV/STI screening, biannual renal function tests and other clinical care as required. Study visits and STI diagnoses will be recorded electronically through the ACCESS surveillance system. At each study visit participants will be invited to complete behavioral surveys that collect demographics and sexual risk data. Diagnosis and behavioral data will be compared between PrEPX participants and other individuals testing within the ACCESS surveillance system. A subset of participants will complete in depth surveys and interviews to collect attitudes, beliefs and acceptability data. Participating clinics will provide clinic level data on implementation and management of PrEPX participants. The population level impact on HIV incidence will be assessed using Victorian HIV notification data. Discussion: This study will collect evidence on the real world impact of delivery of PrEP to 3800 individuals at risk of acquiring HIV in Victoria. This study will provide important information for the broader implementation of PrEP planning upon listing of the tenofovir-emtricitabine on the national subsidized list of medicines. The study is registered on the Australian New Zealand Clinical Trials Registry (ACTRN12616001215415)